2016
DOI: 10.1158/1940-6207.capr-16-0094
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Biosynthesis of Prostaglandin E2 By Low-Dose Aspirin: Implications for Adenocarcinoma Metastasis

Abstract: Meta-analyses have demonstrated that low dose aspirin reduces the risk of developing adenocarcinoma metastasis, and when colon cancer is detected during aspirin treatment, there is a remarkable 83% reduction in risk of metastasis. As platelets participate in the metastatic process, the anti-platelet action of low dose aspirin likely contributes to its anti-metastatic effect. Cycloxooxygenase-2 (COX-2)-derived prostaglandin E2 (PGE2) also contributes to metastasis, and we addressed the hypothesis that low dose … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 69 publications
1
27
1
1
Order By: Relevance
“…Low‐dose aspirin was more effective in acetylating COX‐1 in blood platelets than in colorectal mucosa, despite inhibiting COX‐1 activity with comparable potency in intestinal epithelial cells and platelets in vitro (refs. , and the present study). The exposure of platelets to a higher concentration of intact ASA in the presystemic circulation is a plausible determinant of the higher extent of acetylation of COX‐1 in platelets than colorectal mucosa demonstrated in the present study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Low‐dose aspirin was more effective in acetylating COX‐1 in blood platelets than in colorectal mucosa, despite inhibiting COX‐1 activity with comparable potency in intestinal epithelial cells and platelets in vitro (refs. , and the present study). The exposure of platelets to a higher concentration of intact ASA in the presystemic circulation is a plausible determinant of the higher extent of acetylation of COX‐1 in platelets than colorectal mucosa demonstrated in the present study.…”
Section: Discussionsupporting
confidence: 78%
“…These assessments were secondary endpoints and the statistical power of the clinical study was inadequate to detect moderate treatment effects. Recently, Boutaud et al . reported that low‐dose aspirin reduced urinary PGE‐M and PGI‐M levels by 45% and 37%, respectively, in a larger population of healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there is already proof of principle, albeit unappreciated, for the utility of this concept because an effective “chemoprevention” strategy for CRCLM already exists, namely the use of low dose aspirin. Aspirin (ASA), a negative regulator of prostaglandin E2 signaling via its inhibitory effects on the COX1 and 2 enzymes has now been shown to significantly reduce CRCLM in several epidemiological studies (67). While not completely understood, it is believed that the mechanism of action (MOA) relates to the effect of ASA on COX1 signaling in platelets (68).…”
Section: B Clinical-translational Advancesmentioning
confidence: 99%
“…While not completely understood, it is believed that the mechanism of action (MOA) relates to the effect of ASA on COX1 signaling in platelets (68). In the microvascular phase of LM, platelets may promote metastases by enhancing cancer cell adhesion to EC and leukocytes, thereby facilitating transmigration (67). Platelets may also aid in the evasion of NK surveillance.…”
Section: B Clinical-translational Advancesmentioning
confidence: 99%
“…Phospholipids in the cell membrane are rich in arachidonic acid so when the cells are stimulated by external stimuli, including bradykinin, thrombin, antigen-antibody complexes or other pathological factors, a number of which have not yet been characterized, the phospholipase A2 in cell membrane will be activated, consequently hydrolyzing the phospholipids and releasing arachidonic acid, which may then synthesize PGs under a series of enzymes including COX-2 and PGs synthetase (20). In the majority of normal tissues, PG is not expressed; however, under the stimuli of factors such as cytokines, growth factors, oncogenes or tumor-promoting agents, it may be upregulated and associated with the occurrence and development of tumors (21). Previous study has identified that COX-2 is upregulated in a number of tumor tissues and is associated with tumorigenesis, malignant transformation, resistance or prognosis (22).…”
Section: Discussionmentioning
confidence: 99%